Alpha-lipoic acid in non-proliferative diabetic retinopathy treatment - Tatiana Yul'evna Demidova; Yulia Alexandrovna Trakhtenberg (Сахарный диабет)
Aim. The aim of this study is to assess the therapeutic efficacy of alpha-lipoic acid in patients with type 2 diabetes mellitus (DM) and non-proliferativediabetic retinopathy. Materials and methods. 47 patients with mild to moderate non-proliferative diabetic retinopathy were included in this trial. Dynamics of ophthalmologicparameters were assessed by means of stereoscopic photography of ocular fundus. Patients were examined every 6 months in order to registernew cases of clinically significant macular oedema. Results. During 24 months follow-up period, patients treated with 600 mg of alpha-lipoic acid showed stabilization in development of diabetic retinopathy.New cases of macular oedema, as well as transition into a more severe stage of retonopathy were less common in those patients. Vision andcontrast sensation also remained stable in the majority of participants from experimental group.Conclusions. 600 mg of alpha-lipoic acid may be recommended for patients with type 2 DM as part of complex therapy